Penyuluhan Tentang Pernikahan Dini di RT 008 RW 003 Desa Pematang Bango Kelurahan Curup Jare Kota Pagar Alam - Nursanti, Rina; S, Suprida; R, Rohaya; Elviani, Yeni (Nanggroe: Jurnal Pengabdian Cendikia, 2025)
According to the World Health Organization (WHO), early marriage is a marriage in which one or both partners are still categorized as children or adolescents under the age of 19 years. According to the Indonesian Law No. 1 of 1974, Article 7 paragraph 1, marriage is only permitted if the male has reached the age of 19 years and the female has reached the age of 16 years. If they are below this age, it is referred to as early marriage. In general terms, early marriage is a formal institution that binds two individuals of the opposite sex who are still adolescents into a family relationship. Adolescence itself is a transitional period from childhood to adulthood, during which individuals experience rapid changes in various aspects of life. They are no longer children in terms of physical appearance, attitudes, ways of thinking, and behavior, yet they are not fully mature adults.The factors causing early marriage include economic conditions, education, parental influence, mass media and the internet, pregnancy outside of marriage, customs and culture, and adolescent emotionality. Early marriage is not recommended for several reasons, including an increased risk of sexually transmitted diseases, higher incidence of sexual violence, increased pregnancy risks, psychological problems, and a higher risk of low social and economic status.